WPŁYW PRAKTYK NAUCZYCIELSKICH NA ROZWÓJ REFLEKSYJNOŚCI STUDENTÓW FILOLOGII ANGIELSKIEJ ORAZ NA ICH DALSZE DECYZJE ZWIĄZANE Z WYBOREM ZAWODU NAUCZYCIELA - Derenowski, Marek (Neofilolog, 2019)
Taking part in teaching practice is supposed to help students of English philology make the right decisions concerning their future teaching careers. During their third year of studies they conduct 45 lessons individually. During these teaching hours students have a unique opportunity to put their theoretical knowledge into practice in the classroom and decide if they really want to become teachers in the future. The study presents data obtained from a short questionnaire and group interviews conducted among philology students after their teaching practice. It focuses on the students’ opinions concerning the influence of teaching practice on the development of reflectivity and on the choice of future career. Additionally, students were asked about the possible reasons influencing their decisions about the future.